2022
DOI: 10.1101/2022.12.05.519141
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The large GTPase Sey1/atlastin mediates lipid droplet- and FadL-dependent intracellular fatty acid metabolism ofLegionella pneumophila

Abstract: The facultative intracellular bacterium Legionella pneumophila employs the Icm/Dot type IV secretion system (T4SS) to replicate in a unique membrane-bound compartment, the Legionella containing vacuole (LCV). The endoplasmic reticulum (ER)-resident large fusion GTPase Sey1/atlastin promotes remodeling and expansion of LCVs, and the GTPase is also implicated in the formation of ER-derived lipid droplets (LDs). Here we show that LCVs intimately interact with palmitate-induced LDs in Dictyostelium discoideum amoe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…Less‐well studied intracellular interactions, such as those of LDs with peroxisomes [33,119], pathogens [120–123], and the cytoskeleton [124,125], have been supported by EM observations. Recent investigations into LD–LD contact sites support a model where a potentially phase‐separated Cidec‐condensate facilitates the flux of neutral lipids along an internal pressure gradient from smaller to larger LDs [47,113, 126,150].…”
Section: Characterization Of Lds At the Organelle And Sub‐organelle L...mentioning
confidence: 91%
“…Less‐well studied intracellular interactions, such as those of LDs with peroxisomes [33,119], pathogens [120–123], and the cytoskeleton [124,125], have been supported by EM observations. Recent investigations into LD–LD contact sites support a model where a potentially phase‐separated Cidec‐condensate facilitates the flux of neutral lipids along an internal pressure gradient from smaller to larger LDs [47,113, 126,150].…”
Section: Characterization Of Lds At the Organelle And Sub‐organelle L...mentioning
confidence: 91%
“…The ER‐residing large fusion GTPase Sey1/atlastin 3 promotes LCV expansion and intracellular replication of L. pneumophila (Hüsler et al, 2021; Steiner et al, 2017; Steiner, Weber, Kaech, et al, 2018). Dictyostelium discoideum ∆ sey1 mutant amoeba show pleiotropic defects, including aberrant ER architecture and dynamics, impaired LCV–ER interactions, and intracellular bacterial replication (Hüsler et al, 2021), as well as reduced LCV–LD interactions (Hüsler et al, 2023).…”
Section: Lipid Droplet‐mediated Fatty Acid Metabolism Of Legionella P...mentioning
confidence: 99%
“…A recent study revealed that LCVs intimately interact with palmitate‐induced LDs in D. discoideum , and the large GTPase Sey1 as well as the L. pneumophila Icm/Dot T4SS and the effector LegG1 promote LCV–LD interactions (Hüsler et al, 2023). In vitro reconstitution of LCV–LD interactions using purified LCVs and LDs from D. discoideum Ax3 or Δ sey1 indicated that Sey1 and GTP promote this process.…”
Section: Lipid Droplet‐mediated Fatty Acid Metabolism Of Legionella P...mentioning
confidence: 99%
See 1 more Smart Citation